Життєвий шлях і науково-практична спадщина академіка НАН України П. Г. Костюка - Веселовський, М.С. (Вісник НАН України, 2024)
Speech at the anniversary session of the general meeting of the National Academy of Sciences of Ukraine, dedicated to the 100th anniversary of Academician of the NAS of Ukraine P.G. Kostiuk, September 11, 2024.